m6A Modification-Mediated DUXAP8 Regulation of Malignant Phenotype and Chemotherapy Resistance of Hepatocellular Carcinoma Through miR-584-5p/MAPK1/ERK Pathway Axis - Liu, Zefeng; Lu, Jin; Fang, He; Sheng, Jiyao; Cui, Mengying; Yang, Yongsheng; Tang, Bo; Zhang, Xuewen (Frontiers in Cell and Developmental Biology, 2021)
Hepatocellular carcinoma (HCC) has a poor prognosis due to its high malignancy, rapid disease progression, and the presence of chemotherapy resistance. Long-stranded non-coding RNAs (lncRNAs) affect many malignant tumors, including HCC. However, their mechanism of action in HCC remains unclear. This study aimed to clarify the role of DUXAP8 in regulating the malignant phenotype and chemotherapy resistance in HCC. Using an in vivo xenograft tumor model, the regulatory functions and mechanisms of lncRNA DUXAP8 in the progression and response of HCC to chemotherapy were explored. It was found that DUXAP8 was significantly upregulated in a patient-derived xenograft tumor model based on sorafenib treatment, which is usually associated with a relatively poor prognosis in patients. In HCC, DUXAP8 maintained its upregulation in the expression by increasing the stability of m6A methylation-mediated RNA. DUXAP8 levels were positively correlated with the proliferation, migration, invasion, and chemotherapy resistance of HCC in vivo and in vitro. In the mechanistic study, it was found that DUXAP8 competitively binds to miR-584-5p through a competing endogenous RNA (ceRNA) mechanism, thus acting as a molecular sponge for miR-584-5p to regulate MAPK1 expression, which in turn activates the MAPK/ERK pathway. These findings can provide ideas for finding new prognostic indicators and therapeutic targets for patients with HCC.